NGHIÊN CỨU DỊCH CHUYỂN KIRCHHOFF ĐỂ XÁC ĐỊNH MÔ HÌNH VẬN TỐC TRONG PHƯƠNG PHÁP ĐIỆN TỪ TẦN SỐ CAO - Cường, Lê Văn Anh; Vấn, Nguyễn Thành; Giảng, Nguyễn Văn; Trung, Đặng Hoài; Triết, Võ Minh (Vietnam Journal of Earth Sciences, 2011)
Kirchhoff migration for specifying velocity model in high frequency electromagnetic method The Kirchhoff migration plays an important role in converting seismic data into images of geological layers according to viewpoint in the geophysics. In this paper, the theory of the high frequency electromagnetic method, the Kirchhoff migration and its application in the high frequency electromagnetic method (Ground Penetration Radar) to specifying velocity model are illustrated. The studied results of modelling of a diffraction point are appliedfor processing data of GPR measurements in Ho Chi Minh City.